Uniform sarcolemmal dystrophin expression is required to prevent extracellular microRNA release and improve dystrophic pathology. Issue 2 (17th December 2019) - van Westering, Tirsa L.E.; Lomonosova, Yulia; Coenen‐Stass, Anna M.L.; Betts, Corinne A.; Bhomra, Amarjit; Hulsker, Margriet; Clark, Lucy E.; McClorey, Graham; Aartsma‐Rus, Annemieke; van Putten, Maaike; Wood, Matthew J.A.; Roberts, Thomas C.
Abstract: Background: Duchenne muscular dystrophy (DMD) is a fatal muscle‐wasting disorder caused by genetic loss of dystrophin protein. Extracellular microRNAs (ex‐miRNAs) are putative, minimally invasive biomarkers of DMD. Specific ex‐miRNAs (e.g. miR‐1, miR‐133a, miR‐206, and miR‐483) are highly up‐regulated in the serum of DMD patients and dystrophic animal models and are restored to wild‐type levels following exon skipping‐mediated dystrophin rescue in mdx mice. As such, ex‐miRNAs are promising pharmacodynamic biomarkers of exon skipping efficacy. Here, we aimed to determine the degree to which ex‐miRNA levels reflect the underlying level of dystrophin protein expression in dystrophic muscle. Methods: Candidate ex‐miRNA biomarker levels were investigated in mdx mice in which dystrophin was restored with peptide‐PMO (PPMO) exon skipping conjugates and in mdx‐Xist Δhs mice that express variable amounts of dystrophin from birth as a consequence of skewed X‐chromosome inactivation. miRNA profiling was performed in mdx‐Xist Δhs mice using the FirePlex methodology and key results validated by small RNA TaqMan RT‐qPCR. The muscles from each animal model were further characterized by dystrophin western blot and immunofluorescence staining. Results: The restoration of ex‐myomiR abundance observed following PPMO treatment was not recapitulated in the high dystrophin‐expressing mdx‐Xist Δhs group, despite these animals expressing similar amounts of total dystrophin protein (~37% of wild‐type levels). Instead, ex‐miRNAs were present at high levels in mdx‐Xist Δhs mice regardless of dystrophin expression. PPMO‐treated muscles exhibited a uniform pattern of dystrophin localization and were devoid of regenerating fibres, whereas mdx‐Xist Δhs muscles showed non‐homogeneous dystrophin staining and sporadic regenerating foci. Conclusions: Uniform dystrophin expression is required to prevent ex‐miRNA release, stabilize myofiber turnover, and attenuate pathology in dystrophic muscle.